A corpus-based investigation of pausing and the production of formulaic Language in EAP speech fluency - Wang, Lifang (2019)
Speech fluency and knowledge of formulaic language are interrelated. The relationship between these two aspects is described in this thesis by the Holistic Hypothesis, that is, formulaic sequences are believed to be produced as holistic units, without internal pauses, in naturally occurring discourse. However, this hypothesis is mainly based on impressionistic evidence from adult learner speech. Very few empirical studies have been conducted to examine and compare the production of formulaic language and the presence of internal pauses in large-scale, authentic learner and native speaker data. To fill this gap, this thesis carries out an in-depth, mixed methods, contrastive investigation of the Holistic Hypothesis in two corpora of academic spoken English, one contributed by Chinese EAP learners and the other by native speakers of American English.